1998
DOI: 10.1182/blood.v91.2.458
|View full text |Cite
|
Sign up to set email alerts
|

Early Induction of Apoptosis in Hematopoietic Cell Lines After Exposure to Flavopiridol

Abstract: Flavopiridol (NSC 649890; Behringwerke L86-8275, Marburg, Germany), is a potent inhibitor of cyclin dependent kinases (CDKs) 1, 2, and 4. It has potent antiproliferative effects in vitro and is active in tumor models in vivo. While surveying the effect of flavopiridol on cell cycle progression in different cell types, we discovered that hematopoietic cell lines, including SUDHL4, SUDHL6 (B-cell lines), Jurkat, and MOLT4 (T-cell lines), and HL60 (myeloid), displayed notable sensitivity to flavopiridol-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Flavopiridol was first discovered as a potent growth inhibitor of several breast and lung cancer cell lines (Kaur et al 1992). Different studies have shown that flavopiridol has the potential to inhibit the proliferation of a broad range of different types of cell lines, human tumours, leukaemias and lymphomas (Drees et al 1997;Parker et al 1998). Several phase I and phase II clinical trials with different regimens have been completed.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Flavopiridol was first discovered as a potent growth inhibitor of several breast and lung cancer cell lines (Kaur et al 1992). Different studies have shown that flavopiridol has the potential to inhibit the proliferation of a broad range of different types of cell lines, human tumours, leukaemias and lymphomas (Drees et al 1997;Parker et al 1998). Several phase I and phase II clinical trials with different regimens have been completed.…”
Section: Flavonoidsmentioning
confidence: 99%
“…( Figure 2D), a modification that is an integral event in the induction of p53 by a diverse range of stimuli (Cox and Meek, 2010). Various cell lines, in particular of haematopoietic origin, show pronounced sensitivity to flavopiridol-and/or DRBinduced apoptosis (Konig et al, 1997;Parker et al, 1998;Te Poele et al, 1999). Due to its pro-apoptotic effects, flavopiridol is currently under investigation in phase II clinical trials as a therapeutic agent in acute myelogenous leukaemia (AML) (Karp et al, 2012).…”
Section: Cdk9 Inhibition By Ldc067 Reduces Ser2-p Induces P53 Activamentioning
confidence: 99%
“…Flavopiridol (Alvocidib, NSC 649890), is a serine/threonine kinase inhibitor that broadly targets cyclin-dependent kinases (CDKs), including the cyclin 9/cyclin T complex (pTEF-b), preventing activation of RNA polymerase II [1] – [2] . Flavopiridol initiates cell cycle arrest [3] , [4] and p53-independent apoptosis [5] [6] through down-regulation of Mcl-1 and X-linked inactivator of apoptosis (XIAP) [7] , [8] [9] . These preclinical characteristics provided the rationale for clinical investigation of flavopiridol in chronic lymphocytic leukemia (CLL), as advanced CLL is commonly associated with elevated Mcl-1 and dysfunctional p53, rendering standard treatments such as alkylating agents, fludarabine and rituximab ineffective [10] .…”
Section: Introductionmentioning
confidence: 99%